Study of Shamanic Witchcraft (Santet) Culture in the Indonesian Archipelago - Risma, Olivia (Enigma in Cultural, 2023)
Various ethnic groups in Sumatra also possess shamanic traditions that involve traditional rites and the involvement of shamans or individuals with specialized skills in countering black magic. Each of these ethnic groups possesses distinct practices and beliefs. The Batak tribe has diverse ethnic subgroups, including Toba Batak, Karo, Mandailing, and others. Within Batak culture, there exist shamanistic rituals, and individuals who perform these rituals are referred to as "datu" or "Batak shamans." The shaman has a crucial function in upholding social and spiritual equilibrium within society. They possess the ability to retaliate against dark sorcery or provide healing for ailments through their expertise and spiritual wisdom. The Minangkabau tribe upholds robust traditional customs, which encompass shamanic rituals associated with the veneration of ancestors and nature deities. Within Minangkabau society, there exist individuals known as "bundo kanduang" who possess specialized expertise in countering the effects of black magic and healing ailments by traditional means. The Bukit Barisan tribe is an indigenous population dispersed over the Bukit Barisan region, encompassing a significant portion of Sumatra Island. Their religious system encompasses shamanic ideologies and rituals that revolve around the veneration of nature spirits and ancestral figures. Shamans, or spiritual leaders, play a crucial role in upholding social and spiritual equilibrium within their communities. It is crucial to bear in mind that these shamanic rituals exhibit variations among different ethnic groups and subgroups in Sumatra. Moreover, the impact of religions like Islam and Christianity has also had an influence on certain shamanic activities within these communities. Shamanic practices encompass a range of functions, including customary rituals and endeavors to address societal and metaphysical discord. Gaining insight into this cultural legacy and shamanistic customs enables us to value the cultural variety in Indonesia and the ongoing evolution and adjustment of various cultures in response to changing circumstances.